Medicinal Importance of Pleurotus species (Oyster Mushroom) A review - Fahad Haseeb Irfan; Saman Shafiq; Sayed Afroz; Amina Saleem; Muhammad Ammar (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
Pleurotus ostreatus is a Macro- Fungi. It belongs to the class Basidiomycota and the family Agaricaceae. It is the second-largest cultivated edible mushroom for various purposes like food and medicine. Somehow cardiometabolic parameters and various diseases like cancer can be treated with the intake of mushrooms through diet. In the modern world, oyster mushrooms are known for their high-quality protein, fiber, vitamins and many other healing properties. It is used as a health enhancer, more than any other mushroom. Many biologically active compounds in this mushroom include polysaccharides, lipopolysaccharides, proteins, peptides, glycoproteins, nucleosides, triterpenoids, lectins, lipids and their derivatives.i In this review, an extensive database search and analysis was performed to change the status and to predict the biomedical potential of Oyster mushroom (Pleurotus). (Sarma, Saha et al. 2018)